Leibowitz or God's absence - Horowitz, Daniel, 1945- (Academic Studies Press, 2022)
"As a scientist, philosopher and scholar in Jewish thought, Yeshayahu Leibowitz was one of the most noteworthy Jewish thinkers in the twentieth century. He was endowed with an remarkable intellect and was knowledgeable across a variety of fields. Born in Riga (Latvia) in 1903 he later immigrated to Israel, where he taught Organic chemistry, biochemistry, neurology, biology, neurophysiology, philosophy and Jewish thought at Haifa and Jerusalem University. He was chief editor of the Hebrew encyclopedia, where he wrote about scientific, philosophical, historical and religious topics. Leibowitz was an orthodox Jew but rejected the notion of divine intervention in nature or history. So what was actually Leibowitz' belief ? This is what this book is about"--